PENINGKATAN KAPASITAS DIGITAL SUSI SEPRAI DAN BEDCOVER MELAUI PENDAMPINGAN DAN PEMBUATAN KONTEN VISUAL DI KECAMATAN LUBUK BEGALUNG KOTA PADANG - Komalasari, Sanda Patrisia; Rahman, Annisaa; Kartika, Rayna; Triani, Laura Amelia; Aprilita, Vivi; Alamsyah, Adithya; Alfiqri, Muhammad Rozaq; Tri, Diwah Ganda; Hadelina, Rizka; Mardiah, Ainul; Harzikra, Rafki (LPPM Universitas Andalas, 2024)
This community service activity aims to enhance the digital marketing capabilities of the Susi Seprai and Bedcover MSME by providing assistance and creating visual content in the form of product photos and videos. With high-quality visual content, it is expected to increase product appeal and broaden online marketing reach. The activity is carried out in two phases: a product photography training on August 15, 2024, and visual content creation assistance from August 1, 2024, to October 1, 2024, at the Susi Seprai and Bedcover MSME location in Padang City, West Sumatra. The methods used in this activity include technical training in product photography, an introduction to and use of photo editing applications such as Canva and Photoshop, and video editing applications like Premiere Pro. This training is designed to provide practical knowledge to MSME owners on how to take attractive product photos and edit them for a more professional look. The results of this activity show an improvement in the MSME owner's ability to take and edit photos and videos of their products and to use editing applications like Canva for digital marketing purposes. Additionally, photos and videos have been produced as promotional content. The conclusion of this activity is that training and assistance in visual content creation are effective in enhancing MSME digital marketing capabilities. The recommendation is for further training on other digital marketing techniques and deeper exploration of editing applications to optimize visual content outcomes.